2013
DOI: 10.1126/scitranslmed.3005374
|View full text |Cite
|
Sign up to set email alerts
|

TSLP Elicits IL-33–Independent Innate Lymphoid Cell Responses to Promote Skin Inflammation

Abstract: Innate lymphoid cells (ILCs) are a recently identified family of heterogeneous immune cells that can be divided into three groups based on their differential developmental requirements and expression of effector cytokines. Among these, group 2 ILCs produce the type 2 cytokines IL-5 and IL-13 and promote type 2 inflammation in the lung and intestine. However, whether group 2 ILCs reside in the skin and contribute to skin inflammation has not been characterized. Here, we identify for the first time a population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
793
6
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 654 publications
(818 citation statements)
references
References 39 publications
(90 reference statements)
14
793
6
5
Order By: Relevance
“…They are divided into three groups: group 1 ILCs are IFN-γ-producing cells that include natural killer cells; group 2 ILCs produce IL-13, IL-5, and/or IL-4; and group 3 ILCs produce IL-17 and IL-22 (21). Group 2 ILCs were shown to be significantly increased in human AD lesions, as compared to healthy skin (20).…”
Section: Keratinocyte Dysfunctions In Admentioning
confidence: 99%
See 2 more Smart Citations
“…They are divided into three groups: group 1 ILCs are IFN-γ-producing cells that include natural killer cells; group 2 ILCs produce IL-13, IL-5, and/or IL-4; and group 3 ILCs produce IL-17 and IL-22 (21). Group 2 ILCs were shown to be significantly increased in human AD lesions, as compared to healthy skin (20).…”
Section: Keratinocyte Dysfunctions In Admentioning
confidence: 99%
“…TSLP activates dendritic cells (DC) to produce chemokines such as thymus-and activation-regulated chemokine/ chemokine (C-C motif) ligand (CCL)17 and macrophagederived chemokine/CCL22, which leads to infiltration of Th2 cells in AD lesions (19). In a recent AD mouse model, TSLP was shown to activate cutaneous group 2 innate lymphoid cells (ILCs; Figure 1) (20). ILCs are characterized by their lymphoid morphology, but lack recombination-activating genedependent rearrangement antigen receptors and myeloid/ dendritic cell markers (20).…”
Section: Keratinocyte Dysfunctions In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Cet enrichissement est aussi observé chez les patients atteints de rhinosinusite chronique [1] et dans les lésions inflammatoires de dermatite atopique, chez l'homme comme chez la souris. Leur déplétion atténue les symptômes cutanés chez la souris [49]. Dans les poumons, les ILC2 sont à l'origine de l'inflammation allergique provoquée, dans le modèle murin, par l'administration intranasale de l'allergène papaïne, et de l'hyperréactivité pulmonaire que l'on observe après une infection par le virus de la grippe [23].…”
Section: Les Ilc2unclassified
“…On the other hand, another independent research group has demonstrated that skin-resident ILC2s are indispensible for atopic dermatitis (AD)-like disease induced by the vitamin D3 analog MC903. 6 This chemical is a potent inducer of TSLP (but not IL-25 and IL-33) production by keratinocytes. Which cytokine is produced among IL-25, IL-33 and TSLP at mucosal barriers seems to be determined by types of allergens, parasites and other injury inducers, and responding parenchymal and stromal cells.…”
mentioning
confidence: 99%